Doing Affect Around National Days: Mundane/Banal Practice or the Call of ‘Another Space’? - Mccreanor, Tim; Muriwai, Emerald; Wetherell, M.; Moewaka Barnes, H.; Moewaka Barnes, Angela (Everyday Nationhood: Theorising Culture, Identity and Belonging After Banal Nationalism, 2017)
The intense choreography of a nation’s identity is often exhibited through national days. In Aotearoa, New Zealand, national events such as Waitangi Day (6 February) and Anzac Day (25 April) provide affective public spaces that engage identity, belonging and inclusion while evoking dissent, reverence, unity and division. In this chapter, we analyse the choreography of affect and discourse related to Waitangi Day through media, observational video and focus group data. We explore affective–discursive positions related to Micheal Billig’s notion of banal nationalism, and expand on this through analysis of feelings, emotion, spirituality and the Māori concept, wairua. A social practice lens is used to study ways in which such affective labour contributes to a colonialist everyday nationalism. Findings offer important windows on how nationhood might be critiqued, challenged and diversified to more adequately represent the ongoing dynamics and tensions between Māori and Pākehā.
Keywords: Waitangi Day; memorialisation; memory; nationhood

Same inequities or engaged te tiriti partnership? - Kukutai, T.; McIntosh, T.; Moewaka Barnes, H.; McCreanor, T. (MAI Journal, 2020)
Keywords: community; covid-19; treaty obligations